Integrasi Work-Life Balance dan Manajemen Kinerja terhadap Kepuasan Kerja dan Efektivitas Organisasi: Pendekatan Systematic Literature Review Berbasis PRISMA - Sugiayasin, Risan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to systematically analyze the role of Work-Life Balance and Performance Management in enhancing Job Satisfaction and Organizational Effectiveness through a Systematic Literature Review (SLR) approach. The study employed the PRISMA 2020 protocol in the processes of identification, screening, and synthesis of the literature. The search was conducted across the Scopus, Web of Science, ScienceDirect, Emerald Insight, and SpringerLink databases, covering publications from 2020 to 2025. Out of 420 identified articles, 22 internationally reputable articles met the inclusion criteria and were further analyzed using thematic synthesis techniques. The findings indicate that Work-Life Balance significantly influences Job Satisfaction through mechanisms such as reducing role conflict and enhancing psychological well-being. Meanwhile, transparent Performance Management systems, based on continuous feedback and competency development, directly contribute to improving Job Satisfaction and Organizational Effectiveness. Furthermore, Job Satisfaction acts as a mediating variable that strengthens the relationship between Work-Life Balance and Performance Management practices and organizational effectiveness. This study provides a theoretical contribution by developing an integrative conceptual model that links work-life balance and performance management systems within the framework of Strategic Human Resource Management. Practically, the findings emphasize the importance of integrating employee well-being policies and strategic performance evaluation systems to create productive and sustainable organizations.